2004
DOI: 10.1128/mcb.24.16.7284-7297.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Plant snoRNP Complex Containing snoRNAs, Fibrillarin, and Nucleolin-Like Proteins Is Competent for both rRNA Gene Binding and Pre-rRNA Processing In Vitro

Abstract: In eukaryotes the primary cleavage of the precursor rRNA (pre-rRNA) occurs in the 5 external transcribed spacer (5ETS). In Saccharomyces cerevisiae and animals this cleavage depends on a conserved U3 small nucleolar ribonucleoprotein particle (snoRNP), including fibrillarin, and on other transiently associated proteins such as nucleolin. This large complex can be visualized by electron microscopy bound to the nascent pre-rRNA soon after initiation of transcription. Our group previously described a radish rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(156 citation statements)
references
References 58 publications
3
152
0
1
Order By: Relevance
“…These observations indicate that transcription factors can be mobilized to the site of transcription separately from pre-rRNA processing factors, which are recruited only in the presence of the specific substrate. This suggests that the association of pre-rRNA processing factors to the newly transcribed rRNA is sequential and is on anneeded basis.Our findings that pol I transcription factors interact with pre-rRNA processing factors are consistent with recent studies in nonmammalian systems that found transcription factors in the same complex with pre-rRNA processing factors (Fath et al, 2000;Gallagher et al, 2004) and coordination between the two processes (Veinot-Drebot et al, 1988;Caparros-Ruiz et al, 1997;Dragon et al, 2002;Gallagher et al, 2004;Osheim et al, 2004;Saez-Vasquez et al, 2004). Studies in yeast showed that most nascent pre-rRNA transcripts no longer contain 5Ј external transcribed spacer sequences (Veinot-Drebot et al, 1988) and that the initial steps of pre-rRNA processing take place before the completion of pre-rRNA transcription (Dragon et al, 2002;Osheim et al, 2004).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…These observations indicate that transcription factors can be mobilized to the site of transcription separately from pre-rRNA processing factors, which are recruited only in the presence of the specific substrate. This suggests that the association of pre-rRNA processing factors to the newly transcribed rRNA is sequential and is on anneeded basis.Our findings that pol I transcription factors interact with pre-rRNA processing factors are consistent with recent studies in nonmammalian systems that found transcription factors in the same complex with pre-rRNA processing factors (Fath et al, 2000;Gallagher et al, 2004) and coordination between the two processes (Veinot-Drebot et al, 1988;Caparros-Ruiz et al, 1997;Dragon et al, 2002;Gallagher et al, 2004;Osheim et al, 2004;Saez-Vasquez et al, 2004). Studies in yeast showed that most nascent pre-rRNA transcripts no longer contain 5Ј external transcribed spacer sequences (Veinot-Drebot et al, 1988) and that the initial steps of pre-rRNA processing take place before the completion of pre-rRNA transcription (Dragon et al, 2002;Osheim et al, 2004).…”
supporting
confidence: 81%
“…The coordination between transcription and pre-rRNA processing could be facilitated through at least two different mechanisms. The transcription and processing factors could be corecruited to the site of transcription in a large complex, as the pol II system is coordinated, which is an idea that is supported by a number of published studies (Fath et al, 2000;Saez-Vasquez et al, 2004). Alternatively, processing factors could be recruited to the sites of transcription only when the nascent pre-rRNA substrate becomes available.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Primer extension analysis was performed using total RNA and specific 5Ј-end labeled primers as previously described (Saez-Vasquez et al, 2004). Primers used were tis for detection of primary pre-rRNA precursor (ϩ104 nucleotides from transcription initiation site [TIS]) and p (ϩ1362 nucleotides from TIS) for detection of pre-rRNA cleaved at the P site ( Figure 9A).…”
Section: Methods Related To Rnamentioning
confidence: 99%
“…The extracts were cleared by centrifugation at 13,000 ϫ g for 15 min and conserved at Ϫ80°C. SDS-PAGE, and Western blot was performed as described previously (Saez-Vasquez et al, 2004). The membranes were hybridized with a 1:10,000 dilution of ␣-NUC1 or with a 1:5000 dilution of ␣-NUC2.…”
Section: Western Blottingmentioning
confidence: 99%